Micro-nano aerated subsurface drip irrigation and biochar promote photosynthesis, dry matter accumulation and yield of cucumbers in greenhouse - Zan Ouyang; Jie Zhang; Xueli Liang; Hui Wang; Zhenfeng Yang; Rong Tang; Qihua Yu; Yong Zhang (Agricultural Water Management)
The combination of micro-nano bubble water (MNBW) with subsurface drip irrigation (SDI) is an effective and water-saving aerated irrigation technique. Biochar is a biomass resource with high porosity, alkalinity, and specific surface area. The effects of SDI with MNBW and biochar on crop photosynthetic characteristics, dry matter accumulation, and red soil (clay) aeration are not well understood. Three levels concentrations of dissolved oxygen (DO) in MNBW: O1 (4–5 mg/L), O2 (9–10 mg/L), and O3 (14–15 mg/L), as well as three levels amount of biochar application (BA): B1 (20 t/hm2), B2 (40 t/hm2), and B3 (60 t/hm2), and one control group (CK, O: 4–5 mg/L, B: 0 t/hm2) were the subjects of this study, followed by a two-factor randomized block design. The study examined the aeration practices of the red soil (clay) and the responses of greenhouse-grown cucumbers to SDI over the first and second growing seasons. The concentration of DO in MNBW and the amount of BA had a substantial impact on yield, dry matter accumulation, key quality indicators, photosynthetic characteristics, and soil aeration (P < 0.05). Compared to CK, in the two-season experiment, the average soil aeration porosity (SAP) increased by 0.53–44.00 %, the soil oxygen content (SO) increased by 0.47–31.80 %, the net photosynthetic rate (Pn) increased by 1.91–50.78 %, the dry matter accumulation increased by 10.53–69.19 %, the yield increased by 1.72–44.23 %, and the water use efficiency (WUE) improved by 0.42–76.57 %. Plant dry weight, cucumber yield, irrigation water use efficiency, vitamin C, and the sugar-acid ratio all have a substantial positive correlation (P < 0.05) with the photosynthetic rate. Soil aeration porosity, soil oxygen, photosynthetic rate, plant dry weight, and irrigation water use efficiency all have a substantial positive correlation with yield (P < 0.05). Micro-nano bubble water enhanced the oxygen content and soil aeration porosity, while biochar increased the porosity and lowered the bulk density of the soil. The ''oxidation-porous'' qualities of micro-nano bubble water and biochar combined to enhance clay soil aeration, promote cucumber development, accelerate photosynthetic rate and dry matter buildup, and enhance yield and quality.O3B3 (O3 14–15 mg/L, B3 60 t/hm2) was the optimal treatment when factors like yield and quality were taken into consideration. The research findings provide theoretical basis and feasible approaches for improving the aeration of clay and enhancing the quality and efficiency of greenhouse crops.